Effective knock down of matrix metalloproteinase‐13 by an intra‐articular injection of small interfering RNA (siRNA) in a murine surgically‐induced osteoarthritis model. Issue 9 (22nd May 2014) - Akagi, Ryuichiro; Sasho, Takahisa; Saito, Masahiko; Endo, Jun; Yamaguchi, Satoshi; Muramatsu, Yuta; Mukoyama, Shunsuke; Akatsu, Yorikazu; Katsuragi, Joe; Fukawa, Taisuke; Takahashi, Kazuhisa
ABSTRACT This study investigated the effect of MMP‐13 gene knock down on cartilage degradation by injecting small interfering RNA (siRNA) into knee joints in a mouse model of osteoarthritis (OA). OA was induced in male C57BL/6 mice by destabilization of medial meniscus (DMM) surgery. Change of Mmp13 expression over time was determined by qPCR analysis from 3 days to 6 weeks after surgery. Mmp13 and control chemically modified siRNA were injected into the knee joint 1 week after surgery and expression levels were assessed in synovium by qPCR 48 h later. Cartilage degradation was histologically assessed 8 weeks after DMM surgery according to OARSI recommendations. Mmp13 expression levels were elevated 1 week after surgery and peaked at 77 fold at 2 weeks compared to expression at 3 days. A 55% decrease of Mmp13 levels in cartilage was observed 48 h after injection of Mmp13 siRNA (p = 0.05). Significant reduction in the histological score at 8 weeks after surgery was observed in the Mmp13 siRNA‐treated group compared to the control siRNA group (p < 0.001). Intra‐articular injection of Mmp13 siRNA at the early phase of OA development resulted in effective knock down of Mmp13 expression and delay in cartilage degradation in vivo. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1175–1180, 2014.